Disruption of Tumor Necrosis Factor Receptor-Associated Factor 5 Exacerbates Murine Experimental Colitis via Regulating T Helper Cell-Mediated Inflammation - Jian Shang; Lixia Li; Xiaobing Wang; Huaqin Pan; Shi Liu; Ruohang He; Jin Li; Qiu Zhao (Mediators of Inflammation)
Tumor necrosis factor (TNF) receptor-associated factor 5 (TRAF5) is a key mediator of TNF receptor superfamily members and is important in both T helper (Th) cell immunity and the regulation of multiple signaling pathways. To clarify TRAF5’s influence on inflammatory bowel diseases (IBDs), we investigated TRAF5 deficiency’s effect on dextran sulfate sodium- (DSS-) induced colitis. Colitis was induced in TRAF5 knockout (KO) mice and their wild-type (WT) littermates by administering 3% DSS orally for 7 days. The mice were then sacrificed, and their colons were removed. Our data suggested that KO mice were more susceptible to DSS-induced colitis. TRAF5 deficiency significantly enhanced IFN-γ, IL-4, and IL-17a mRNA and protein levels in the colons of DSS-fed mice, and the mRNA expression of T-bet and GATA-3 was also markedly elevated. However, ROR-α and ROR-γt mRNA levels did not differ between DSS-induced KO and WT mice. Flow cytometry showed increased frequencies of Th2 and IFN-γ/IL-17a-coproducing CD4+ T cells in the colons of DSS-induced KO mice. Additionally, TRAF5 deficiency significantly enhanced the activation of NF-κB in CD4+ T cells after DSS administration. These results indicated that TRAF5 deficiency significantly aggravated DSS-induced colitis, most likely by regulating Th cell-mediated inflammation.